Nutritional composition, antioxidant activity and hypotensive effect of brown seaweed (Sargassum polycystum) enriched bread - Noraidah Haini (2017)
Hypertension is a major risk factor of cardiovascular diseases globally. Studies have shown that there is a positive association between seaweed intake and lower blood pressure as indicated in animal studies as well as limited human trials. Hence, this study was designed to investigate the hypotensive effect of Sargassum polycystum (SP) enriched bread on blood pressure among pre-hypertensive subjects. In this open label crossover trial, 12 subjects were randomly divided into two groups, who later received seaweed bread and control bread for 8 weeks with two months washout period. 5. po/ycystum powder (5 - 25%) was incorporated with wheat flour in producing yeast breads. These formulated breads were examined for their nutritional composition, antioxidant activities and sensory acceptance. The study showed that nutritional values of seaweed breads were significantly different from the control bread (p<0.05); wherein SP enriched breads contained ash ( 1.16 - 4.74%), moisture (34.65 - 37.57%), crude fat (6.45 - 6.98%), crude protein (8.74 - 8.92%), dietary fibre (2.26 - 9.71 %) on dry weight basis, besides having significant composition of macro minerals (Na, K, Ca and Mg) content. Ethanolic extracts of S. polycystum enriched breads possessed significantly higher total phenolic content (5.34 - 13.85 mg PGE/g dry extract), ferric reducing antioxidant power (FRAP) (122.89 - 162.06 μM FE/g dry extract) and DPPH radical scavenging activity (2.09 - 9.07 mg/ml) than water extracts (p<0.05). Sensory evaluation of breads using hedonic test has shown that bread enriched with 10% SP powder was selected as the best formulation among all seaweed breads (p<0.05), whereby its shelf life test showed that it is safe for 7-day consumption. In vitro test of antihypertensive assay showed that SP powder (0.41 mg/ml) and 10% seaweed bread (3.13 mg/ml) possessed higher ACE-inhibitor capacities than the control bread (25.01 mg/ml) (p<0.05). Intervention trial showed that subjects consuming seaweed bread resulted in significantly lower systolic blood pressure, diastolic blood pressure, pulse and total cholesterol (p<0.05). On contrary, subjects consuming control bread showed that there was no significant change in diastolic blood pressure but their systolic blood pressure, pulse and total cholesterol were significantly higher than the baseline (p<0.05). On the whole, the new therapeutic discovery of hypotensive effect in SP powder would contribute to health-promoting properties of seaweed as well as providing useful information to local industries for potential development of food and health products.